Incidence of nevus pigmentosus and malignant melanoma at the Department of Anatomical Pathology, Faculty of Medicine Gadjah Mada University - AAGP Wiraguna, AAGP Wiraguna (Universitas Gadjah Mada, 1994)
The incidence of malignant melanoma (MM) varies in several countries. The differences include sex, age, and location. It is suggested, therefore, that there is an association between incidence of MM and pigmented nevi (PN) based on sex, age, and its location in the population.A restrospective study has been carried out at Dr. Sardjito General Hospital and Department of Anatomical Pathology, Faculty of Medicine Gadjah Mada University, Yogyakarta from January 1986 to December 1989 to determine the frequency, sex, age, and its location. The incidence of MM and PN were analysed by, sex, age, location, and the possible association. The study found that the incidence of MM and PN in male and female were 1:1,5 and 1:3,4 respectively. The peak of age in female were at the age of 45-49 and 55-59 year, however, in male the peak of incidence was at the age of 45-49 group. Male and female has similar localisation of incidence. Females have more frequent lesion on the lower extremities (25%), and equal number on the head and neck, mink and upper extremities compared to males. In both sexes, PN was mosty found on the head and neck (male 76.5%, and female 75.7%).Key Words: pigmented nevi-malignant melanoma -sex ratio-sun exposure-aging